Miocene–Recent evolution of the western Antalya Basin and its linkage with the Isparta Angle, eastern Mediterranean - Hall, J.; Aksu, A. E.; Çi̇fci̇, Günay; King, H.; Yaltırak, Cenk; Gogacz, A. (Elsevier BV, 2014)
Abstract Interpretation of ~ 9500 km of multichannel seismic reflection profiles showed the presence of two major tectonic histories in western Antalya Basin, spanning from the Miocene (or older) to the Pliocene–Quaternary. A prominent fold–thrust belt affects the Miocene succession in the offshore. The thrusts swing from a NW–SE strike, with SW vergence, in the northeast of the mapped area to a more northerly strike, with westerly vergence at the western shelf edge of the deep basin. The Miocene deformation appears to continue offshore from the westerly-directed thrusting seen onshore that characterizes the eastern edge of the Isparta Angle. The contraction is consistent with the counterclockwise Miocene rotation of the western side of the Isparta Angle determined from paleomagnetic studies. The thrust belt forms the western extremity of the wider regional Aksu–Kyrenia–Misis oroclinal culmination. The tectonic activity experienced a period of relative quiescence across the western Antalya Basin during the Messinian. A major kinematic change occurred in the Pliocene, when the regional strain was partitioned into three spatially localized tectonic domains: an extensional domain confined to the Pliocene–Quaternary Unit 1, occupied the northeastern portion of the study area, a predominantly extensional domain with a few re-activated pre-existing Miocene contractional structures occupied the southern and central portion of the study area, and an extensional and/or transtensional domain occupied the continental shelf and slope in the westernmost Antalya Basin. These complexities relate to strike-slip motions as the crustal block within the Isparta Angle moved northwards relative to the blocks to the north.